Analisis dan Optimalisasi Jaringan Nirkabel dengan Minimalisasi Roaming di Binus Square - Antonius Herusutopo; Audi Eka Prasetyo; Marco Stefanus; Admiral Wiem (ComTech: Computer, Mathematics and Engineering Applications, 2014)
The presence of a notebook/netbook that is practical and has a high mobility makes internet connection is not only done through a single cable connection. High levels of human mobility, require an internet connection with a high mobility as well, this is encouraging the development of wireless internet connection in Indonesia. The purpose of this study is to analyze the wireless network at Binus Square today and then optimize by minimizing roaming. The method of this study begins with data collection, analysis design, testing and evaluation. The method that is used is to measure bandwidth, to measure the speed and stability of data transfer when it is roaming, and then to measure the transfer speed and stability with wireless network system. From this study it can be seen that the wireless network can be a network of high-speed and stable. This study concluded that based on the simulation, this condition is quite fulfilling.